Environmentally‐ and human‐induced body‐size responses in Macropus robustus and Macropus rufus, two widespread kangaroo species with largely overlapping distributions. (1st November 2017) - Correll, Rachel A.; Prowse, Thomas A. A.; Prideaux, Gavin J.
Abstract: Progressive body‐size dwarfing of animal populations is predicted under chronic mortality stress, such as that inflicted by human harvesting. However, empirical support for such declines in body size due to elevated mortality is lacking. In fact, the size of three macropodid species ─ the two grey kangaroo species, Macropus fuliginosus and M. giganteus, and the Red‐necked Wallaby, M. rufogriseus ─ appears to have increased since European settlement in Australia, despite these species being subjected to size‐selective harvesting over this period. To test whether this unexpected trend also characterises other species, we sought evidence of human‐induced body‐size changes in the two most widely distributed kangaroo species, the Euro Macropus robustus and Red Kangaroo M. rufus, from the late 19th Century onwards. Spatial autoregressive models controlling for age, sex and island effects were first used to identify environmental predictors of body size and to evaluate multi‐causal explanations for spatial body‐size patterns. Primary productivity emerged as the key driver of body size in both species, while heat conservation was supported as a further mechanism explaining the large body size of M. robustus in cold climatic regions. After controlling for these environmental factors, we find that the size of M. rufus has been stable over time and limited support for a small increase in the size of M. robustus . Hence, there is no empirical evidence that contemporary size‐selective harvesting has reduced body size in these species. Rather, the latter result supports the possibility that pasture improvement and/or dingo control (and associated reduction in predation pressure) facilitated body‐size increases following European settlement in Australia.